2016
DOI: 10.2319/031716-227.1
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-year follow-up of mandibular incisor stability: Comparison between two bonded lingual orthodontic retainers

Abstract: Objective: To compare the long-term outcome 9 years after removal of two different types of fixed retainers used for stabilization of the mandibular anterior segment. Materials and Methods: Sixty-four children who had undergone orthodontic treatment with fixed appliances in both arches were divided into two groups depending on which kind of retainer being used. Twenty-eight of the patients had a canine-to-canine retainer bonded to the canines and 36 had a bonded twistflex retainer 3-3, bonded to each tooth. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Plaster models were measured in 0.01 mm units using a digital caliper (Mitutoyo, Kanagawa, Japan) for all measurements. The 13 measured items included the maxillary and mandibular intercanine widths, mandibular intercanine perimeter distance, lateral arch lengths from the maxillary and mandibular central incisors to first molars, sum of the widths of the mandibular four incisors, available mandibular incisor space (intercanine perimeter distance minus the sum of the widths of the four incisors), maxillary inter‐first molar width (distance from central sulcus to central sulcus of the upper first molars), overjet, and overbite; these items were presumably related to mandibular anterior crowding based on the findings of previous studies (Figure 1; Louly, Nouer, Janson, & Pinzan, 2011; Schutz‐Fransson, Lindsten, Bjerklin, & Bondemark, 2017). Additionally, Little's irregularity index (LII) was measured; this was defined as the sum of displacement of the anatomic contact points of the mandibular anterior teeth (Figure 2).…”
Section: Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…Plaster models were measured in 0.01 mm units using a digital caliper (Mitutoyo, Kanagawa, Japan) for all measurements. The 13 measured items included the maxillary and mandibular intercanine widths, mandibular intercanine perimeter distance, lateral arch lengths from the maxillary and mandibular central incisors to first molars, sum of the widths of the mandibular four incisors, available mandibular incisor space (intercanine perimeter distance minus the sum of the widths of the four incisors), maxillary inter‐first molar width (distance from central sulcus to central sulcus of the upper first molars), overjet, and overbite; these items were presumably related to mandibular anterior crowding based on the findings of previous studies (Figure 1; Louly, Nouer, Janson, & Pinzan, 2011; Schutz‐Fransson, Lindsten, Bjerklin, & Bondemark, 2017). Additionally, Little's irregularity index (LII) was measured; this was defined as the sum of displacement of the anatomic contact points of the mandibular anterior teeth (Figure 2).…”
Section: Methodsmentioning
confidence: 81%
“…Co., Ltd., Kyoto, Japan) in accordance with the manufacturer's instructions and were traced. Cephalometric reference points and measurements were assessed following the method of Schutz‐Fransson et al (2017). Reference lines and points are shown in Figure 3, and the following 11 measurement items were recorded: 1.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that the stability of the mandibular interincisor region may only be guaranteed if retainers are maintained throughout life. 13 , 14 The need for maintaining the intercanine distance is emphasized, as it undergoes changes with age, irrespective of orthodontic treatment. The question remains whether the retainers should be bonded to all the incisors, or whether it would be acceptable for them to be bonded only to the canines.…”
Section: Discussionmentioning
confidence: 99%
“…2 , 7 , 8 Nevertheless, apparently retainers bonded to mandibular anterior teeth have presented worst periodontal indexes than those observed for retainers bonded to the canines only. 9 - 14 However, when there is excessive misalignment of the incisors before orthodontic treatment, it appears to be rational to stabilize them individually, considering the probable dissatisfaction of patients in case of short term instability. 2 , 4 , 7 , 8 , 15 , 16 Another alternative is to inform the patient about the possibility of instability in the area, and adopt classical retainers bonded to the canines only, and if any alteration should occur, proceed with localized correction, followed by new stabilization.…”
Section: Introductionmentioning
confidence: 99%
“…If dropouts occur at the 5-year follow-up registration and the LOCF method is applied, the registrations for the 2-year follow-up have to be used for those subjects who dropped out at the 5-year registration. However, it is well known from previous studies regarding incisor stability that the Little Irregularity Index worsens in the long term (21,22). Consequently, when the LOCF procedure is applied, the risk is clear that the kept Little Irregularity Index at the 2-year follow-up registration (now also used as the 5-year registration) will be lower than it would have been if the subject had been maintained at the trial registration as planned at the 5-year follow-up.…”
Section: Advice On How To Best Handle Missing Data or Dropoutsmentioning
confidence: 97%